Prevalence of Acquired Carbapenemase Genes in Klebsiella Pneumoniae by Multiplex PCR in Isfahan - Farzin Khorvash; Mohammed Reza Yazdani; Ali Asghar Soudi; Shiva Shabani; Nirvana Tavahen (Advanced Biomedical Research, 2017)
Background: Multi-drug resistant Klebsiella pneumoniae has been considered as a serious global threat. This study was done to investigate carbapenemase producing genomes among K. pneumoniae isolates in Isfahan, Central Iran. Materials and Methods: In a cross-sectional study from 2011 to 2012, 29 carbapenem resistant (according to disc diffusion method) carbapenemase producing (according to modified Hodge test) K. pneumoniae strains were collected from Intensive Care Unit (ICUs) of Al-Zahra referral Hospital. In the strains with the lack of sensitivity to one or several carbapenems, beta-lactams, or beta-lactamases, there has been performed modified Hodge test to investigate carbapenmase and then only strains producing carbapenmases were selected for molecular methods. Results: In this study, there have been 29 cases of K. pneumoniae isolated from hospitalized patients in the (ICU). Three cases (10.3%) contained blaVIM, 1 case (3.4%) contained blaIMP, and 1 case (3.4%) contained blaOXA. The genes blaNDM and blaKPC were not detected. Then, 16 cases (55.2%) from positive cases of K. pneumoniae were related to the chip, 4 cases (13.8%) to catheter, 6 cases (20.7%) to urine, and 3 cases (10.3%) to wound. Conclusion: It is necessary to monitor the epidemiologic changes of these carbapenemase genes in K. pneumoniae in our Hospital. More attention should be paid to nosocomial infection control measures. Other carbapenemase producing genes should be investigated.